(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
This paper publishes an edition of some Public records (1213-1276) once belonged to St. Radegonda monastery and now kept at the halle University Library. This is an addition to Gli atti del comune di Milano nel secolo XIII by Maria Franca Baroni, Roberto Perelli Cippo and more recently by Luca Fois.